1994
DOI: 10.1080/07315724.1994.10718433
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of a Mg-enriched diet and different orally administered magnesium oxide preparations on ionized Mg, Mg metabolism and electrolytes in serum of human volunteers.

Abstract: These results indicate that since serum IMg2+ and % IMg2+, but not TMg, can be altered by dietary intake, previous or future findings which may indicate no change in TMg by diet may not reflect changes in biologically-active Mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 12 publications
2
28
2
Order By: Relevance
“…However, Johansson and Whiss [55] reported that the correlation of ionized Mg (iMg2 + ) and total Mg in serum is weak. Altura et al [56] also found that short-term dietary elevations in Mg intake can result in a significant elevation of serum ionized Mg, although total serum Mg is unaffected. Therefore, the beneficial effects of dietary Mg might be mediated by higher concentrations of ionized Mg, which is not measured at the present study.…”
Section: Discussionmentioning
confidence: 96%
“…However, Johansson and Whiss [55] reported that the correlation of ionized Mg (iMg2 + ) and total Mg in serum is weak. Altura et al [56] also found that short-term dietary elevations in Mg intake can result in a significant elevation of serum ionized Mg, although total serum Mg is unaffected. Therefore, the beneficial effects of dietary Mg might be mediated by higher concentrations of ionized Mg, which is not measured at the present study.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies suggest that populations consuming low levels of Mg are at greater risk for cardiovascular disease than populations consuming diets enriched in Mg [4][5][6][7]. While it is difficult to assess the incidence of Mg deficiency (MgD) in the general population due to the lack of universally accepted testing methods, standard clinical laboratory techniques have shown that hypomagnesemia is a common condition in hospitalized patients: 63% of intensive care patients exhibited hypomagnesemia [8], and 45% of patients with acute myocardial infarction had hypomagnesemia [9]. Mgwasting also occurs in other segments of the population (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies suggest that populations consuming low levels of Mg 2ϩ are at greater risk of morbidity after a myocardial ischemic response episode than populations consuming enriched Mg 2ϩ (Leary, 1986;Rylander et al, 1991). Hypomagnesemia is also common in hospitalized patients: 63% of intensive care patients exhibited hypomagnesemia (Altura et al, 1994), and 45% of patients with acute myocardial infarction had low Mg 2ϩ levels (Vormann et al, 1983). Mg 2ϩ wasting also occurs in other segments of the population, such as diabetics, alcoholics, human immunodeficiency virus-infected patients, leading to overt hypomagnesemia (Altura and Altura, 1985;Dubey and Solomon, 1989;Seelig, 1989).…”
mentioning
confidence: 99%